Faktor Risiko Kejadian Hipertensi Pada Pasien Perempuan Di Wilayah Puskesmas Simpang Timbangan - Nadroh, Yutini; Yulianto; Muzakar; Podojoyo; Sartono (Politeknik Kesehatan Kemenkes Bengkulu, 2024)
One of the most significant factors in global mortality and morbidity rates is hypertension. Based on Riskesdas findings, the incidence of hypertension in Indonesia has increased, namely from 25.8 percent in 2013 to 34.1% in 2018 in residents aged over 18 years. The absolute number of female hypertension sufferers is found in the Simpang Timbangan Community. Welfare Center regional group, 56.25% were female patients aged between 25 - 54 years. The aim of this study was to identify risk factors for hypertension in female patients. Case-control research design is a research method. The population of this study consisted of 72 respondents, namely 36 case respondents and 36 control respondents. The scalable test uses a modern framework with the chi square factual test. Results: Statistical tests (chi square) showed that there was a relationship between the prevalence of hypertension and knowledge (OR=18.182), family history (OR=12.5), and sodium intake (OR=7.995), but there was no relationship. between the tools used and the prevalence of hypertension. Hormonal contraception with the occurrence of hypertension (OR=0.571). In conclusion, the prevalence of hypertension in female patients in the Simpang Timbangan Community Health Center area is related to knowledge, family history, and sodium consumption.